2010
DOI: 10.1089/gtmb.2009.0142
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-Methyltransferase Gene Polymorphisms Are Not Associated with Multisomatoform Disorder in a Group of German Multisomatoform Disorder Patients and Healthy Controls

Abstract: The etiology of multisomatoform disorder (MSD) is largely unknown, but genetic disposition may be one of several risk factors. As pain is a major component of MSD, and polymorphisms in the catechol-O-methyltransferase (COMT) gene are associated with COMT enzymatic activity and pain sensitivity, we assumed that COMT polymorphisms could be associated with MSD. One hundred and forty-nine patients with MSD and 149 age- and sex-matched healthy controls participated in this study. The inclusion criteria for MSD were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…These patients show a higher prevalence of psychiatric comorbidity, worse functioning, and impaired symptom improvement compared with individuals without the disorder [88]. A recent study attempted to elucidate the possible genetic risk factors of this relatively unknown disease by exploring the association between six SNPs in the COMT gene, including rs4680 [58]. None of the SNPs investigated was found to be associated with multisomatoform disorder.…”
Section: Miscellaneous Studiesmentioning
confidence: 99%
“…These patients show a higher prevalence of psychiatric comorbidity, worse functioning, and impaired symptom improvement compared with individuals without the disorder [88]. A recent study attempted to elucidate the possible genetic risk factors of this relatively unknown disease by exploring the association between six SNPs in the COMT gene, including rs4680 [58]. None of the SNPs investigated was found to be associated with multisomatoform disorder.…”
Section: Miscellaneous Studiesmentioning
confidence: 99%
“…Subjects. The patient collective was previously investigated regarding the role of single nucleotide polymorphisms [6][7][8] as well as the difference in quantitative sensory profiles and epigenetic regulation of TRPA1 expression between patients and controls [9,11]. Altogether, 300 individuals were recruited to participate (151 patients, 149 controls).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were screened for possible MSD through demonstrating a PHQ-15 score > 10 and a 36-Item Short-Form 36 (SF-36) physical component score ≤ 40 which demonstrates strong psychophysiological strain as established previously [3]. Additionally, a modified interview of the somatoform disorder section of the Structured Clinical Interview of the DSM-IV (SCID) was used [1,3,[6][7][8]. The interview (SCID) was modified to check for published diagnostic criteria of MSD [1,3] and required three currently present somatoform symptoms in addition to one pain-related symptom which are functionally disabling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very recently, a population-based twin study of FSS showed that those symptoms, especially chronic widespread pain, are affected by genetic influences (Kato et al, 2009). While catechol-O-methyltransferase polymorphisms seem to account for part of the variability among the pain responses of individuals (Edwards, 2006), such an association could not be demonstrated in either in FMS (Sommer et al, 2008) or in MSD ( Jacobi et al, 2010). The serotonergic and the dopaminergic systems appear to be strongly associated with the clinical picture (Sommer, 2006) and pharmacological approaches (Lawson, 2008) in FMS.…”
Section: Introductionmentioning
confidence: 99%